Metode Pembelajaran Bahasa Arab di MI: (Studi Kasus Metode Eklektik di MI Swasta Terpadu Al-Hidayah Medan Tembung) - Alga, Riska Kalidya; Panggabean, Khairan Nur; Sinaga, Ifah Auliah; Sundari, Dewi; Hsb, Azka Amalia Ashari; Harahap, Widya Amelita Dewi Asri; Nadeak, Siti Rahayu; Azhara, Selvyra; Sapri, Sapri (Khazanah : Journal of Islamic Studies, 2023)
The purpose of this study is to ascertain how Arabic language instruction is implemented at the madrasah level using a range of media. This information will subsequently affect the four competences that students need to master: reading (Qira'ah), writing (scroll), speaking (kalam), and listening (Istima'). This study employed a qualitative approach as its technique, gathering data through observation and interviews. The study's findings indicate that: 1. Arabic language learning resources are available at Medan Private Al Hidayah Integrated Madrasah Ibtida'iyah, including teaching aids, LCDs, blackboards, and Arabic language package books. Additionally, Arabic teachers have created support materials like vocabulary cards, picture cards, short stories, Arabic boards, grammar boxes, learning videos, and Arabic language packages with songs. 2). How to use Arabic language learning media at Medan Integrated Private MI A l Hidayah varies, such as adjustments to the learning objectives, the material taught, the learning methods used, and even the use of learning media, which are also varied according to the student's condition, so that it has an impact on providing understanding to students regarding the material that has been taught, the emergence of student motivation, eroding students' boredom, improving memory, and increasing students' creativity in the learning process.